(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Drainage as a place for dirty water to flow becomes a trash can which causes blockages in waterways and culverts and results in flooding during the rainy season. The partner’s problem is how to manage the environment well so that the community can live in a clean and healthy environment. Water needs must be met every day while the government neglects to pay attention to the needs of the community. This problem is what makes implementing community service important to implement. The aim of implementing community service activities is to create a clean living environment and fulfill adequate water needs.The implementation method are: a) Gathering mothers in one fellowship or through the Women’s Worship Fellowship of the GMIM Pniel Watulambot Congregation.b). Explanation of community service c) . Environmental cleanliness which is contested in ecclesiastical holiday activities (Easter Feast) d) Counseling regarding household water needs e) Counseling on drainage cleanliness.The result is that the group of mothers understands environmental cleanliness and water needs and does this every day. In conclusion, it is important to maintain environmental cleanliness and fulfill water needs.